Revulcanization Kinetics of Waste Tire Rubber Devulcanized by Microwaves: Challenges in Getting Recycled Tire Rubber for Technical Application - De Sousa, Fabiula Danielli Bastos; Zanchet, Aline; Ornaghi Júnior, Heitor Luiz [UNESP]; Ornaghi, Felipe Gustavo (American Chemical Society (ACS), 2019)
Recycling is a process toward sustainable development. However, it does not do any good to recycle a material trying to contribute to the environment, if the final properties of the recycled material do not point to a feasible application. In this sense, the purpose of the present study is to evaluate the kinetics parameters of the revulcanization reaction of ground tire rubber (GTR) devulcanized by microwaves using rheological (ODR) and differential scanning calorimetry (DSC) methods. For ODR, torque versus time curves was obtained at 160, 170, 180, 190, and 200 °C and simulated. In general, occurred a decrease in activation energy values upon microwaves exposure time but all the samples showed an autocatalytic model from simulation curves. For DSC, three different models were used: Kissinger, Ozawa, and Flynn-Wall-Ozawa. All of the methods showed a trend to decrease the activation energy by microwave exposure time as noticed in the rheological curves. Among the reasons, the carbon black and the viscosity of the system are the main contributors; the former by radiation tends to oxidize and facilitates the degradation process, and the latter achieves more facility to chain mobility, reducing the activation energy.
Keywords: Devulcanization; Ground tire rubber; Kinetics; Microwaves; Revulcanization